The emperor Augustus and the Theater of Marcellus: the representation of the theater in the Roman urban space (1st century BC) - Aga Pereira Passos, Letícia (Romanitas - Revista de Estudos Grecolatinos, 2022)
In the transitional period between Republic and Principate, Roman’s urban image was used by Emperor Augustus as a means of legitimizing both his new government and his own image. As an heir of Julius Caesar, the Princeps aim was to modernize the city by building grand public monuments, particularly the southern shore of the Campus Martius, which was promoted to the experimental category and, on account of it, received various constructions. Among these is that of the Theater of Marcellus, one of the largest theaters in the Roman Empire. Despite the logical changes inherent over time and the restorations carried out, the monumental structure of the theater remains to the present day. Thus, by deepening the study of the physical space of the theater, we seek to reflect on the construction of Marcellus’ Theater, highlighting the importance of its location within the Urbs’ planning. By seeking to convey an image of power, as well as that of a good princeps, Augustus built the Campus Martius almost as a showcase for imperial architecture and the physical manifestation of Roman’s prominence.